INSTITUTIONAL AND SPATIAL EFFECTS ON MANUFACTURING PERFORMANCE IN CENTRAL JAVA PROVINCE: THE NEW INSTITUTIONAL ECONOMICS AND THE NEW ECONOMIC GEOGRAPHY PERSPECTIVE - Abdul Aziz Ahmad; Prasetyo Soepono; Wihana Kirana Jaya (Journal of Indonesian Economy and Business (JIEB), 2013)
In the economic view, the manufacturing sector is important in relationship to its role in economicgrowth and the whole economy. This empirical work examines why manufacturing disparityexists, and what institutional and spatial factors empirically have an important effect onthe manufacturing sector development in Central Java Province, Indonesia. The variables thatare identified that have an influence on the manufacturing performance are ethno linguistic,legal rules, bureaucratic financial performance, democracy, city fascination, regional locationindex, the manufacturing base, infrastructure, the labor force, the intermediary finance institutionand the types of regional administration (regency and city). To analyze it, this researchuses the spatial econometric method on its methodological analyses. It is used to reduce thepotential problem that arose in the cross section and panel data which had spatial interaction,and spatial structure. This empirical work shows that all of the institutional variables havepositive and significant effects on the dependent variable. The other result is that every spatialvariable also tends to have a positive and significant impact on manufacturing development.For economic policy, labor activity, the roles of financial intermediaries and infrastructurevariables also have a positive effect on the manufacturing development.Keywords: manufacturing disparity, spatial econometrics, institutional, ethno linguistic,regional location index